Introducing Slag Powder as Drag Reduction Agent in Pipeline: An Experimental Approach - Abdulbari, Hayder A.; Siti Nuraffini, Kamarulizam; R. M., Yunus; Gupta, Arun (Academic Journals, 2012)
Main by product in ore smelting from tin production in Malaysia has become a trigger for this investigation. Slag waste can be categorized as suspended solid. Utilization of this waste in fluid transportation can reduce the pressure drop in pipelines. Experimental works had conducted in order to test slag waste in a closed loop of turbulence water flowing system with water and fuel as the transport liquid. The procedures start by pumping liquid suspended solid combination from reservoir tank with varies flow rates into two different pipe diameters (0.0127 m ID and 0.038 m D.I). The types of pipe used are PVC pipe. The testing length of this flow system is 2.0 m. The pressure drop and drag reduction were measured in varied addition concentration. The results have show percentage drag reduction (Dr%) is over 60% in certain range and condition. It is proved that slag is a potential DRA.